Nos rastros de algoritmos pela cidade: cartografia do desenvolvimento do pensamento computacional na perspectiva da educação OnLife - Menezes, Janaína (Universidade do Vale do Rio dos Sinos, 2022)
The present doctoral research is related to the development of computational thinking in the city in a context of OnLIFE Education. In the problematization of the present time, the research question emerges: How can computational thinking be enhanced in the city? This thesis aims to understand how computational thinking can be developed, leveraged and produced with and in the city. The thesis articulates, from a theoretical-epistemological perspective, inventive cognition (KASTRUP), urban and post-urban spaces (LA ROCCA, DI FELICE, SCHLEMMER), constructionism (PAPERT, LOPES, VALENTE), Heritage Education (SILVA), gamified learning projects (SCHLEMMER), OnLIFE Education (SCHLEMMER AND MOREIRA) and studies on the development of computational thinking, in addition to research results developed by GPe-dU UNISINOS/CNPq. The research uses the Cartographic Research-Intervention Method proposed by Passos, Kastrup, Escóssia and Tedesco for the production and analysis of data. As research instruments, it presents records in photos, audio and video recordings and transcripts, interviews and a field diary. As results, clues are presented that indicate computational thinking being potentiated beyond the human, in an inventive and co-engineered path between human and non-human entities, based on experiences in the city. The thesis contributes to the interdisciplinary and transversal understanding of computational thinking in the context of K-12 Education, the problematization of pedagogical practices in the context of connectivity and digitality and the development of learning spaces that seek to overcome dualisms and centralities.
Keywords: Pensamento computacional; Cidade; Cibricidade; Educação patrimonial; Educação OnLIFE; Computational thinking; City; Cibricity; Heritage education; OnLIFE education; ACCNPQ::Ciências Humanas::Educação